Numerical investigation of the dynamic response of optimized composite elliptical submersible pressure hull subjected to non-contact underwater explosion. (March 2015) - Fathallah, Elsayed; Qi, Hui; Tong, Lili; Helal, Mahmoud
Abstract: Predicting the dynamic response of a floating and submerged structure subjected to underwater explosion is greatly complicated by the explosion of a high explosive, propagation of shock wave, bubble-pulse and complex fluid–structure interaction (FSI) phenomena. A numerical simulation has been carried out to examine the behavior of optimized composite elliptical submersible pressure hull to non-contact underwater explosion (UNDEX) and take the effect of bubble-pulse. Various explosive weights and explosion distances were explored to determine the critical weights and safe distance. The optimization process is performed using ANSYS parametric design language (APDL). After that the finite element package ABAQUS was used to model the UNDEX and the FSI phenomena. Time histories of the wet-surface displacement, velocity and Tsai–Hill failure index are presented for different composite plies. All of these results can be a valuable reference for designing underwater vehicles to resist UNDEX.